2018
DOI: 10.1002/cre2.102
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gum chewing exercise on maximum bite force according to facial morphology

Abstract: Development of the masticatory system is influenced by functional needs. Furthermore, masticatory exercise can improve masticatory function. The aim of this study was to evaluate the potential effect of the gum chewing exercise on the maximum bite force (MBF) in adult subjects with different facial morphologies. MBF was measured by a portable occlusal force gauge and lateral cephalogram was used for evaluation of craniofacial morphology in 19 individuals (7 males and 12 females) with a mean age of 25.4 years (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 18 publications
3
17
0
1
Order By: Relevance
“…It has been reported that gum chewing exercise enhance bite force and masticatory function. 6 , 7 , 8 , 9 , 10 , 11 Kiliaridis et al. 6 reported that 4-week training with hard chewing gum influenced the functional capacity of the masticatory muscles and increased their strength.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been reported that gum chewing exercise enhance bite force and masticatory function. 6 , 7 , 8 , 9 , 10 , 11 Kiliaridis et al. 6 reported that 4-week training with hard chewing gum influenced the functional capacity of the masticatory muscles and increased their strength.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, the maximum bite force of healthy subjects with normal occlusion increased from 468 N to 574 N after 4-week gum chewing exercise. 11 Furthermore, Kato et al. 12 reported that masticatory exercise with gum chewing of 5 min twice a day for 90 days starting at 6 months after surgery improved masticatory efficiency and maximal occlusal force in patients with jaw deformities.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a standard part of the method, resistance training induces myophysiological changes, such as activation and thickness gain of muscles [ 9 , 10 , 11 ]. Several studies have reported that chewing exercises improve motor function during chewing and increase the maximum occlusal force in children, older adults, and patients with neurological disorders [ 2 , 12 , 13 ]. It is hypothesized that the increased activation of the masticatory muscles through resistance training contributes positively to the physiological changes, such as increased muscle thickness and to the maximum occlusal force of the masseter muscle as a result of its repeated use.…”
Section: Introductionmentioning
confidence: 99%